2016
DOI: 10.1016/j.joi.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Clustering by publication patterns of senior authors in the social sciences and humanities

Abstract: This study uses cluster analysis as a tool for mapping diversity of publication patterns in the social sciences and humanities (SSH). By algorithmic clustering of 1828 senior authors affiliated with 16 disciplines at five universities in Flanders, Belgium, based on the similarity of their publication patterns during 2000-2011, we distinguish two broad publication styles, both of which are present within each discipline. We conclude that diversity in SSH publication patterns cuts across disciplinary boundaries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…When considering metrics use at the field level, we acknowledge that the low number of responses limits the authority of our findings. Nevertheless, they support previous work relating to citation coverage and publication practices for Psychology, which used metrics (citations and h‐index) in the highest proportions, and Law, which used citation‐based tools (h‐index and impact factor) least (Butler, ; Verleysen & Weeren, ). It seems likely that Law's much higher use of ranked journal lists is the flip‐side of the low metrics use for the field.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When considering metrics use at the field level, we acknowledge that the low number of responses limits the authority of our findings. Nevertheless, they support previous work relating to citation coverage and publication practices for Psychology, which used metrics (citations and h‐index) in the highest proportions, and Law, which used citation‐based tools (h‐index and impact factor) least (Butler, ; Verleysen & Weeren, ). It seems likely that Law's much higher use of ranked journal lists is the flip‐side of the low metrics use for the field.…”
Section: Discussionsupporting
confidence: 85%
“…The diverse publishing practices of the social sciences limits the use of indicators and metrics in the social sciences. Books, book chapters, reports, conference papers, and a range of others are not uncommon publication forms (Engels, Ossenblok, & Spruyt, 2012;Gumpenberger, Sorz, Wieland, & Gorraiz, 2016;Huang & Chang, 2008;Laudel & Gläser, 2006;Lindholm-Romantschuk & Warner, 1996;Verleysen & Weeren, 2016) and only a tiny proportion of these are covered by Web of Science and Scopus, the most important citation indexes. Over the last decade, the potential for alternative metrics to play a role in evaluating a range of publication types has been proposed; however, the new metrics have yet to prove themselves as credible tools .…”
Section: Bibliometrics Indicators and Research Evaluation In The Somentioning
confidence: 99%
“…It is, for instance, completely possible that a publication written in a language for a small audience contains the same ideas as publications written in English for an audience that is equally scholarly but cannot otherwise be reached. Sivertsen () recently showed that authors tend to diversity their publication outlets simultaneously (see also Verleysen & Weeren, ). His findings thus suggest that it is highly problematic to understand each publication independently from all others.…”
Section: Methodsmentioning
confidence: 99%
“…However, Hammarfelt (2016: 115) observes a shift from investigating coverage issues towards studying the characteristics of SSH publication practices and developing bibliometric approaches sensitive to the organization of SSH research fields. This includes, but is not limited to, extending bibliometric analyses to non-source items (Butler and Visser, 2006;Chi, 2014) or the relatively new Book Citation Index (Gorraiz et al, 2013), using other databases like Google Scholar (Kousha and Thelwall, 2009) or data from social media services, the so-called altmetrics (Holmberg and Thelwall, 2014;Mohammadi and Thelwall, 2014;Zuccala et al, 2015;Zuccala and Cornacchia, 2016), analysing the inclusion in library catalogues (White et al, 2009), exploring national databases with full coverage , extending data to references in research grant proposals (Hammarfelt, 2013) or to book reviews (Zuccala and van Leeuwen, 2011;Zuccala et al, 2015), exploring collaboration (Ossenblok and Engels, 2015) and publication patterns (Chi, 2012;Ossenblok et al, 2012;Verleysen and Weeren, 2016). From a more pragmatic point of view, attempts are made to "weigh" the various outputs, such as journals or books in the SSH, similar to the journal impact factor, commonly used in the sciences (Giménez-Toledo, 2016).…”
Section: Improving the Databasesmentioning
confidence: 99%